2020
DOI: 10.1021/acs.jafc.0c03037
|View full text |Cite
|
Sign up to set email alerts
|

FtMYB6, a Light-Induced SG7 R2R3-MYB Transcription Factor, Promotes Flavonol Biosynthesis in Tartary Buckwheat (Fagopyrum tataricum)

Abstract: Tartary buckwheat (Fagopyrum tataricum) is rich in flavonols, which are thought to be highly beneficial for human health. However, little is known about the regulatory mechanism of flavonol biosynthesis in Tartary buckwheat. In this study, we identified and characterized a novel SG7 R2R3-MYB transcription factor in Tartary buckwheat, FtMYB6. We showed that FtMYB6 is located in the nucleus and acts as a transcriptional activator. The FtMYB6 promoter showed strong spatiotemporal specificity and was induced by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…R2R3-MYB TFs are important regulators of flavonoid biosynthesis. The light-induced transcriptions of flavonoid biosynthesis-related TFs have been observed in various plants, such as Arabidopsis thaliana [ 33 ], Fagopyrum tataricum [ 34 ], and pear [ 35 ]. In our study, top five TFs that have the most interactions with individual flavonoid compounds were MYB12 (TEA009412.1), MYB86 (TEA015433.1), C1 (TEA004608.1), MYB4 (TEA033191.1), and KTN80.4 (TEA033903.1).…”
Section: Discussionmentioning
confidence: 99%
“…R2R3-MYB TFs are important regulators of flavonoid biosynthesis. The light-induced transcriptions of flavonoid biosynthesis-related TFs have been observed in various plants, such as Arabidopsis thaliana [ 33 ], Fagopyrum tataricum [ 34 ], and pear [ 35 ]. In our study, top five TFs that have the most interactions with individual flavonoid compounds were MYB12 (TEA009412.1), MYB86 (TEA015433.1), C1 (TEA004608.1), MYB4 (TEA033191.1), and KTN80.4 (TEA033903.1).…”
Section: Discussionmentioning
confidence: 99%
“…The extraction and measurement of Pas were carried out as previously described in [ 51 ]. High-performance liquid chromatography (HPLC) was performed to determine the rutin content according to the description from Yao [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is widely reported that R2R3-MYB transcription factors play essential roles in the regulation of flavonoid biosynthesis (Xu et al, 2015). In Tartary buckwheat, SG4, SG5, SG6, SG7 subfamily MYBs are responsible for this process (Zhang et al, 2017(Zhang et al, , 2018(Zhang et al, , 2019Li et al, 2019c;Yao et al, 2020;Ding et al, 2021). In order to learn more about the genes in the regulatory network of flavonoid biosynthesis, we collected all DEGs annotated to flavonoid biosynthesis genes and SG4, SG5, SG6, SG7 subfamily MYBs and resulting in 12 flavonoid biosynthesis DEGs and nine MYB DEGs (Figure 4A).…”
Section: Myb Transcription Factor Regulated Flavonoid Biosynthesismentioning
confidence: 99%
“…Proanthocyanidins are catalyzed by dihydroflavonol 4-reductase (DFR), leucoanthocyanidin reductase (LAR), and anthocyanidin reductase (Saito et al, 2013;Chen and Li, 2016;Tohge et al, 2017). Massive flavonoid biosynthesis and regulation are characterized by involving enzyme encoding genes and families of transcription factors, including R2R3-MYB, bHLH, and WD40 proteins, and their interactions (MYB-bHLH-WD40 complex) (Kelemen et al, 2015;Xu et al, 2015;Zhang et al, 2018Zhang et al, , 2019Li et al, 2019c;Sun et al, 2020;Yao et al, 2020;Ding et al, 2021).…”
Section: Introductionmentioning
confidence: 99%